Investigating the construct of motor competence in middle childhood using the BOT‐2 Short Form: An item response theory perspective. (21st August 2019) - Bardid, Farid; Utesch, Till; Lenoir, Matthieu
Abstract : Purpose: Motor assessments generally produce a single motor competence score based on the general motor ability hypothesis, which states that motor competence is a one‐dimensional trait underlying a wide range of motor skills. Yet, it is unclear whether the general motor ability hypothesis holds true in middle childhood, which is marked by an increased participation in sports and other types of physical activity. Therefore, the aim of the study was to evaluate the structure of motor competence in middle childhood using a test battery with a large item set. Method: A cross‐sectional design was used to collect motor competence data of 2538 children aged 6‐11 years. Participants completed the Bruininks‐Oseretsky Test of Motor Proficiency—2nd Edition Short Form (BOT‐2 SF), which consists of 14 skill items and covers different motor domains. In accordance with the BOT‐2 SF manual, point scores were computed for each item. Polytomous Rasch analyses (ie, general partial credit model) were carried out to investigate the construct of motor competence. Results: Rasch analyses revealed different items with unordered threshold parameters, due to ceiling effects. However, after empirically rescaling the category width for each item, follow‐up analyses revealed a one‐dimensional structure with 12 items. Conclusion: The study provides some evidence of a one‐dimensional construct (ie, motor competence) underlying motor assessment in middle childhood. Continued efforts should be made to ensure that valid composite scores are used in motor assessment and to better understand the development of motor competence across childhood and into adolescence and adulthood.